STILISTIKA ARAB DAN KONSEP TEORI AL-NAZM DALAM PEMIKIRAN AL-JAHIZ - Aidy, Muhammad Ulil; Wahyuni Lestari, Sri (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This article examines the theoretical concept of al nazm in Al-Jahiz's thought in the field of Arabic stylistics. In this article, the author presents Al-Jahiz's views on the use of language and how to arrange sentences in Arabic. This study uses a descriptive method using a qualitative approach to understand Al-Jahiz's views in developing the concept of al-Nazm's theory. The results showed that Al-Jahiz understood the concept of al nazm as a method for arranging sentences in Arabic so as to give an aesthetic impression and facilitate understanding. In addition, Al-Jahiz also emphasized the importance of understanding the context and purpose of using language in determining the appropriate style of language. This article has a significant engagement for the study of Arabic language and literature, especially for those who are trying to understand the ideas of al-nazm and how to apply them to compose beautiful and functional sentences. This research can be a basis for further research on the theoretical idea of al nazm in the field of Arabic stylistics.